Extracellular acidification by Saccharomyces cerevisiae in normal and in heavy water - Kotyk, A; Lapathitis, G (Folia microbiologica, 1998)
Titratable acidity of the extracellular medium was compared with that calculated from pH changes in a suspension of Saccharomyces cerevisiae. After addition of cells to normal water the ratio of titratable acidity to the computed one was about 25, after addition of 50 mmol/L D-glucose it was about 13, after subsequent addition of K+ ions it was only 2. In heavy water the respective values were 30, 9, and 1. Apparently, the principal buffer-generating processes have to do with glucose metabolism but little with the K+/H+ exchange observed after addition of K+. D2O appears to block processes producing the buffering capacity of the medium, among them possibly extrusion of organic acids.
Keywords: koncentrace vodíkových iontů; Saccharomyces cerevisiae; chlorid draselný; kyseliny; Potassium Chloride; Deuterium Oxide; Hydrogen-Ion Concentration; Buffers; oxid deuteria; Acids; pufry